Chlorpyrifos residue level and ADHD among children aged 1–6 years in rural China: A cross-sectional study - Zhou, Wenjuan; Deng, Yuanying; Zhang, Chen; Dai, Hongmei; Guan, Lan; Luo, Xiangwen; He, Wei; Tian, Jing; Zhao, Lingling (Frontiers in Pediatrics, 2022)
Background: Attention-deficit/hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorders in childhood and is caused by both genetic and environmental factors. As genetic factors are nonmodifiable, environmental factors have attracted increasing attention. Objective: To investigate the relationships between urinary chlorpyrifos (CPF) levels, blood micronutrient levels, and ADHD prevalence in children living in rural areas of China. Methods: This cross-sectional study collected data on CPF exposure (according to urinary levels), blood micronutrient levels, and ADHD prevalence in children aged 1–6 years in rural China. The CPF levels were determined by mass spectrometry. Blood levels of micronutrients, including zinc, iron, calcium, copper, magnesium, and vitamin D, were measured by professional detection kits. ADHD was diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition. Descriptive statistics and univariate analysis were conducted using SPSS 21.0, and path analysis was conducted using Mplus 8.0. Results: Of the 738 children who met the eligibility criteria, 673 children (673/738, 91.2%) were included in the final analysis. Baseline questionnaires and urine samples were collected from all 673 subjects. A total of 672 children provided blood samples for micronutrient testing, and 651 completed the ADHD assessment. Approximately one-fifth of children (144/673, 21.4%) had detectable levels of CPF in their urine, and 6.9% (45/651) were diagnosed with ADHD. Path analysis showed that the total effect of CPF exposure on ADHD risk was 0.166 (P<0.05), with a direct effect of 0.197 (P<0.05) and an indirect effect of -0.031 (P<0.05) via vitamin D. The mediating effect of urinary CPF levels on ADHD risk via vitamin D was 18.67%. Conclusion: Higher levels of CPF exposure are associated with higher risk of ADHD. Additionally, increasing vitamin D levels may have a beneficial effect on the relationship between CPF exposure and ADHD risk. Our findings highlight the importance of modifying environmental factors to reduce ADHD risk and provide insight into future ADHD interventions.